Simultaneous Graph Drawing: Layout Algorithms and Visualization Schemes - Erten, Cesim; Kobourov, Stephen; Le, Vu; Navabi, Armand (Journal of Graph Algorithms and Applications, 2005)
In this paper we consider the problem of drawing and displaying a series of related graphs, i.e., graphs that share all, or parts of the same node set. We present three algorithms for simultaneous graph drawing and three visualization schemes. The algorithms are based on a modification of the force-directed algorithm that allows us to take into account node weights and edge weights in order to achieve mental map preservation while obtaining individually readable drawings. The algorithms and visualization schemes have been implemented and the system can be downloaded at http://simg.cs.arizona.edu/. <!—->